Change and continuity in sibling relationships from childhood to emerging adulthood: a qualitative study - Bakkaloğlu, Tuğçe Merve Aytaç (İstanbul Bilgi Üniversitesi, 2021)
ABSTRACT: Many studies have been conducted on sibling relationships, yet a few of them have examined the nature of sibling relationships and their transformation and continuity in different developmental periods. Studies of sibling relationships in different developmental periods have been included in recent literature. In this study, relationships between siblings were investigated in the context of childhood and emerging adulthood. The changes and continuities in their relationship dynamics were also examined through their narratives. The present study was carried out by using theme analysis, a qualitative research method, by referring to the experiences of 14 participants with 7 sibling pairs consisting of older and younger siblings between 18-25 years of age. The results of this study showed that sibling relationships develop positively from childhood to emerging adulthood. It has been found that conflicts between siblings during childhood continued into adulthood, but the disagreements were decreased over time. In young adulthood, siblings used the conflict resolution skills of their parents that they have observed in their childhood. The results indicated that siblings communicated less in young adulthood due to various life events. However, their relationships were not negatively affected; on the contrary, they had closer, more sharing, and mature relationships. Their sibling relationships became more egalitarian in young adulthood, like a friendship. The roles of the older and the younger siblings in the relationship were preserved in specific contexts, possibly under the influence of cultural factors. The study also found differences in relationship dynamics such as topics that couses quarrels and the topics that older siblings’ give support to younger ones between same-sex sibling dyads. Sibling relationship studies in Turkey have increased in recent years. There was, however, insufficient research covering the emerging adulthood period. The present study was an attempt to fill this gap in the literature. The results will provide some important information for future researchers and clinicians who will be working with sibling relationship problems.

ÖZET: Kardeş ilişkileri üzerine birçok çalışma yapılsa da, bunlardan birkaçı kardeş ilişkilerinin doğasını, farklı gelişim dönemlerindeki değişimlerini ve sürekliliklerini incelemiştir. Ancak son yıllarda farklı gelişim dönemlerinde kardeş ilişkilerini inceleyen çalışmalar, literatürde yer bulmaya başlamıştır. Bu çalışmada, kardeşler arası ilişkiler, çocukluk ve beliren yetişkinlik bağlamında incelenmiştir. İlişki dinamiklerindeki değişim ve süreklilikler de anlatılar üzerinden incelenmiştir. Bu çalışma, nitel araştırma yöntemlerinden tema analizi kullanılarak, 18-25 yaş arası büyük ve küçük kardeşlerden oluşan 7 kardeş çifti ile 14 katılımcının deneyimlerine başvurularak gerçekleştirilmiştir. Sonuçlar, kardeş ilişkilerinin çocuktan beliren yetişkinliğe olumlu yönde geliştiğini göstermektedir. Çocukluk döneminde, kardeşler arasında yaşanan çatışmalar, yetişkinlik döneminde de devam etmiş ancak çatışma sıklığı azalmıştır. Ayrıca kardeşler, çocukluklarında gözlemledikleri ebeveynlerinin çatışma çözme becerilerini, genç yetişkinlik döneminde kullanmışlardır. Sonuçlar, kardeşlerin çeşitli yaşam olayları nedeniyle genç yetişkinlik döneminde daha az iletişim kurduklarını, ancak ilişkilerinin olumsuz etkilenmediği; aksine daha yakın, daha paylaşımcı ve olgun ilişkilere sahip olduklarını göstermiştir. Beliren yetişkinlik döneminde kardeş ilişkileri, bir arkadaş ilişkisi gibi, hiyerarşik olarak daha eşitlikçi bir yapıya bürünmüştür. Ancak, büyük ve küçük kardeşlerin ilişkideki rolleri, muhtemelen kültürel faktörlerin etkisi altında, belirli bağlamlarda korunmuştur. Araştırmada aynı cinsiyetten kardeşler arasında kavgaya neden olan konular ve büyük kardeşlerin küçüklere destek verdiği konular gibi dinamiklerde farklılıklar bulunmuştur. Türkiye'de kardeş ilişkisi çalışmaları son yıllarda artış göstermiştir. Ancak beliren yetişkinlik dönemini kapsayan yeterli araştırma yoktur. Bu çalışma, literatürdeki bu boşluğu doldurmaya yönelik bir girişimdir. Sonuçlar, gelecekteki araştırmacılar ve kardeş ilişkisi sorunlarıyla çalışacak klinisyenler için bazı önemli bilgiler sağlayacaktır.
Çocukluktan beliren yetişkinliğe kardeş ilişkilerindeki değişimler ve devamlılıklar: nitel bir çalışma
Keywords: Sibling Relationships; Childhood; Emerging Adulthood; Change; Continuity; Kardeş İlişkileri; Çocukluk; Beliren Yetişkinlik; Değişim; Devamlılık